2012
DOI: 10.1289/ehp.1204976
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Methylmercury, Postnatal Lead Exposure, and Evidence of Attention Deficit/Hyperactivity Disorder among Inuit Children in Arctic Québec

Abstract: Background: Prenatal exposure to methylmercury (MeHg) and polychlorinated biphenyls (PCBs) has been associated with impaired performance on attention tasks in previous studies, but the extent to which these cognitive deficits translate into behavioral problems in the classroom and attention deficit/hyperactivity disorder (ADHD) remains unknown. By contrast, lead (Pb) exposure in childhood has been associated with ADHD and disruptive behaviors in several studies.Objectives: In this study we examined the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
114
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 175 publications
(130 citation statements)
references
References 59 publications
(66 reference statements)
7
114
1
4
Order By: Relevance
“…Recently, Boucher et al (2012) reported the association between prenatal MeHg exposure and ADHD symptomatology at school age, corroborating previous results on the effects of MeHg on attention and learning skills (Grandjean et al 1997;Debes et al 2006). Moreover, the association with ADHD-related behaviors seem to be stronger in boys than in girls, which is consistent with the growing evidence showing differences in the impact of endocrine-disrupting chemicals (including mercury) on neurodevelopment in males and females (Sagiv et al 2012).…”
Section: Effects On the Central Nervous System Of Childrensupporting
confidence: 84%
“…Recently, Boucher et al (2012) reported the association between prenatal MeHg exposure and ADHD symptomatology at school age, corroborating previous results on the effects of MeHg on attention and learning skills (Grandjean et al 1997;Debes et al 2006). Moreover, the association with ADHD-related behaviors seem to be stronger in boys than in girls, which is consistent with the growing evidence showing differences in the impact of endocrine-disrupting chemicals (including mercury) on neurodevelopment in males and females (Sagiv et al 2012).…”
Section: Effects On the Central Nervous System Of Childrensupporting
confidence: 84%
“…Prenatal mercury exposure is associated with an increased risk of neurobehavioral disorders, and lead exposure in childhood has been associated with ADHD [51]. In this study, lead and mercury consumption was positively correlated with the traditional-healthy dietary pattern, but it did not alter the beneficial effects of the traditional-healthy dietary pattern on ADHD.…”
Section: Discussionmentioning
confidence: 47%
“…A maioria das crianças com PHDA não foram expostas ao chumbo e muitas crianças com elevada exposição a este metal não desenvolvem a perturbação (Banerjee et al, 2007;Scassellati, Bonvicini, Faraone, & Gennarelli, 2012). Esta hipótese está longe de ser consensual e requer maior evidência empírica (Boucher et al, 2012;Yoshimasu, Kiyohara, Takemura, & Nakai, 2014).…”
Section: Outros Fatores Etiológicos Com Origem Pré Peri E Pós-natalunclassified